2020
DOI: 10.3390/nu12030872
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Pharmacological Activities of Garlic (Allium sativum L.): A Review

Abstract: Medicinal plants have been used from ancient times for human healthcare as in the form of traditional medicines, spices, and other food components. Garlic (Allium sativum L.) is an aromatic herbaceous plant that is consumed worldwide as food and traditional remedy for various diseases. It has been reported to possess several biological properties including anticarcinogenic, antioxidant, antidiabetic, renoprotective, anti-atherosclerotic, antibacterial, antifungal, and antihypertensive activities in traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
253
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 564 publications
(336 citation statements)
references
References 116 publications
2
253
0
6
Order By: Relevance
“…S-Methylcysteine (SMC) is a naturally active component of many Allium plants such as onion, garlic, and leek [ 21 , 22 , 23 ]. Previous studies investigated the anti-protozoal activity of garlic extracts and its phytochemicals against several protozoal diseases including cryptosporidiosis [ 44 ]. However, our study is considered the first to report the protective effects induced by s-Methylcysteine against the intestinal hepatic, splenic, and hepatic damage resulting from the infection by C. parvum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S-Methylcysteine (SMC) is a naturally active component of many Allium plants such as onion, garlic, and leek [ 21 , 22 , 23 ]. Previous studies investigated the anti-protozoal activity of garlic extracts and its phytochemicals against several protozoal diseases including cryptosporidiosis [ 44 ]. However, our study is considered the first to report the protective effects induced by s-Methylcysteine against the intestinal hepatic, splenic, and hepatic damage resulting from the infection by C. parvum .…”
Section: Discussionmentioning
confidence: 99%
“…GSH- and GSH-dependent enzyme, GPx, could be restored after SMC treatment in diabetic rats explaining the antioxidant property of SMC and its ability to conserve the cell components from free radical injuries [ 29 ]. Furthermore, The potential antioxidant effect of garlic extract was clarified in a previous report, that demonstrated an increase of SOD activity and other antioxidants due to the presence of different flavonoids and sulfur compounds as SMC in garlic that have high radical scavenging activities [ 44 ]. This effect may be correlated to the ability of SMC to inhibit NADPH oxidase pathway through down-regulation of p 47phox and gp 91phox expressions, which are components of the NADPH oxidase enzyme, subsequently depressing ROS production [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other related indications of garlic preparations (fresh, garlic powder) included diaphoretic, antiseptic, bacteriostatic, and antiviral effects. It is also used to treat chronic bronchitis and recurrent upper respiratory tract infections (EMA, 2017b;El-Saber Batiha et al, 2020b).…”
Section: Allium Sativum L -Amaryllidaceae (Bulbs Powder)mentioning
confidence: 99%
“…Garlic (Allium sativum) is an aromatic herbaceous plant that has been extensively used worldwide, especially in the Far East, for centuries, in many food dishes due to its appetising property, bitter taste and the flavour it gives to dishes. Despite the use of garlic being such a common practice, this particular plant is of great medical importance, as garlic has exhibited antibacterial, antiviral, antifungal and even antitumor effects [36]. With more than 200 chemical substances, garlic has the ability to protect the human body from many illnesses.…”
Section: Antiviral Properties Of Herbsmentioning
confidence: 99%
“…Despite researchers arguing in order for garlic to be effective, it should be consumed fresh; some research has proven that the effects of garlic are consistent when it is cooked, with oils even providing better protection against oxidative stress and infections [37]. A. sativum is rich in alliin, allicin, ajoenes, vinyldithiins and flavonoids such as quercetin, all of which are sulphur-containing phytoconstituents [36]. Very little work has been done to investigate the antiviral properties of A. sativum but the experiments that have been conducted have shown that A. sativum is effective against influenza B, herpes simplex viruses, cytomegalovirus, rhinovirus, HIV, HSV type 1 and 2 and viral pneumonia [38,39].…”
Section: Antiviral Properties Of Herbsmentioning
confidence: 99%